Mental Health Implications of the COVID-19 Pandemic Among Children and Adolescents: What Do We Know so Far? - Listernick ZI; Badawy SM (Dove Medical Press, 2021)
Zoe I Listernick,1,2 Sherif M Badawy3,4 1Ann & Robert H. Lurie Children's Hospital of Chicago, Chicago, IL, USA; 2Department of Medical Education, Northwestern University Feinberg School of Medicine, Chicago, IL, USA; 3Division of Hematology, Oncology, and Stem Cell Transplantation, Ann & Robert H. Lurie Children's Hospital of Chicago, Chicago, IL, USA; 4Department of Pediatrics, Northwestern University Feinberg School of Medicine, Chicago, IL, USACorrespondence: Sherif M BadawyDivision of Hematology, Oncology, and Stem Cell Transplant, Lurie Ann & Robert H. Children's Hospital of Chicago, 225 E. Chicago Ave., Chicago, IL, 60611, USATel +1 800-543-7362Email sbadawy@luriechildrens.orgAbstract: The COVID-19 pandemic is an unprecedented time in global history and has many emerging challenges and consequences. While much of the world was focused on the physiological effects and medical interventions or preventions, this article highlights the effects on pediatric mental health. While research is still ongoing, preliminary data suggest a significant impact on the psychosocial wellbeing of the pediatric population. This article hopes to highlight the underlying etiology for this effect and possible mitigations including emphasis on mHealth as well as the future of telemedicine.Keywords: pediatric, children, adolescents, infants, youth, coronavirus, COVID, COVID-19, pandemic, mental, mental health, psychosocial, psychiatry, psychology, stress, well-being, depression, anxiety, social isolation, social media, racism, digital, mhealth, ehealth, mobile health, interventions, parenting, parents